Double layer coatings: a new technique for maintaining physico-chemical characteristics and antioxidant properties of dragon fruit during storage - Ali, Asgar; Zahid, Noosheen; Manickam, Sivakumar; Siddiqui, Yasmeen; Alderson, Peter G. (Springer, 2014)
A double layer coating was evaluated for maintenance of quality of dragon fruit during storage at 10 ± 2 °C and 80 ± 5 % RH for 28 days. Significant differences (p < 0.05) were observed between control and the treated fruit. However, a double layer coating with 600 nm droplet size + 1.0 % conventional chitosan showed promising results in all the tested parameters, while the fruit treated with 1,000 nm droplet size + 1.0 % conventional chitosan showed some negative effects on fruit surface. Increase in weight loss was 12.0 % in fruit treated with 600 nm droplet size and 1.0 % conventional chitosan as compared to the control. Antioxidants and gaseous analysis also proved the efficacy of double layer coatings with 600 nm droplet size + 1.0 % conventional chitosan. Thus it can be concluded from the present investigation that double layer coating could be used for maintaining quality in dragon fruit for up to 28 days without any off-flavours.